Efficacy of Vedolizumab for Refractory Pouchitis of the Ileo-anal Pouch: Results From a Multicenter US Cohort. Issue 9 (27th February 2019) - Gregory, Martin; Weaver, Kimberly N; Hoversten, Patrick; Hicks, Stephen Bradley; Patel, Devin; Ciorba, Matthew A; Gutierrez, Alexandra M; Beniwal-Patel, Poonam; Palam, Sowmya; Syal, Gaurav; Herfarth, Hans H; Christophi, George; et al.
Abstract: Background and Aims: Inflammation of the pouch after ileal pouch-anal anastomosis (IPAA) can significantly impact quality of life and be difficult to treat. We assessed the effectiveness and safety of vedolizumab in Crohn's disease (CD) of the pouch and chronic antibiotic-dependent or antibiotic-refractory pouchitis. Methods: This was a retrospective, multicenter cohort study at 5 academic referral centers in the United States. Adult patients with endoscopic inflammation of the pouch who received vedolizumab were included. The primary outcome was clinical response at any time point. Secondary outcomes included clinical remission, endoscopic response, and remission. Univariate analysis and multivariate analysis were performed for the effect of the following variables on clinical response: fistula, onset of pouchitis less than 1 year after IPAA, younger than 35 years old, gender, previous tumor necrosis factor inhibitor-alpha use, and BMI >30. Results: Eighty-three patients were treated with vedolizumab for inflammation of the pouch between January 2014 and October 2017. Median follow-up was 1.3 years (interquartile range 0.7–2.1). The proportion of patients that achieved at least a clinical response was 71.1%, with 19.3% achieving clinical remission. Of the 74 patients with a follow-up pouchoscopy, the proportion of patients with endoscopic response and mucosal healing was 54.1% and 17.6%, respectively. Patients who developed pouchitis symptoms less than 1 year after undergoing IPAA were less likely to respond to vedolizumab, even after controlling for other risk factors. Conclusions: Vedolizumab is safe and effective in the management of CD of the pouch and chronic pouchitis. Further studies are needed to compare vedolizumab with other biologic therapies for pouchitis and CD of the pouch. Abstract : In a multicenter cohort study of 83 patients treated with vedolizumab for pouchitis and Crohn's of the pouch, 71% achieved clinical response, 19.3% clinical remission, whereas endoscopic response and mucosal healing were observed in 54.1% and 17.6%, respectively.